In honor and tribute to Dušan Cotič: Last chairman of the glorious United Nations Commitee on crime prevention & control - Vetere Eduardo (Temida, 2012)
This paper describes the accomplishments of the Commitee on crime prevention & control. Its focus is on the functions discharged by its last Chairman Dušan Cotič before, during and after the Eight Congress held in Havana, and in the following months leading to the formal establishment of the Commission on Crime Prevention and Criminal Justice.